Effects of the TWA strategy on expository reading comprehension of students with autism. (March 2016) - Howorth, Sarah; Lopata, Christopher; Thomeer, Marcus; Rodgers, Jonathan
Abstract : High‐functioning students with autism spectrum disorder (ASD) have been shown to have significant reading comprehension difficulty. This multiple baseline study examined the effect of the think before reading, think while reading, and think after reading (TWA) strategy on expository text comprehension of four boys with ASD. Following baseline, each student received six sessions of TWA instruction. Data were collected on retell and comprehension question accuracy during the baseline, intervention and maintenance phases. Results supported the effectiveness of TWA as a reading strategy to increase the expository text comprehension of students with ASD. Effects during the intervention phase were immediate and consistent for comprehension questions, with greater variability observed for retell. Data collected at maintenance suggested that the gains were sustained for both comprehension questions and retell.